2012
DOI: 10.3998/ark.5550190.0013.113
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of tryptanthrin and its derivatives

Abstract: Tryptanthrin (indolo[2,1-b]quinazoline-6,12-dione) is a natural product which shows significant biological activity as an antibacterial, antiparasitic, and antineoplastic agent. Historically, tryptanthrin has been found as a component of many dyes as well as a constituent of medicinal herbal treatments. This review describes the synthesis of tryptanthrin and some related compounds which also have a quinazoline ring fused to an indolo moiety as a core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…T, T2F, and DCM-T were synthesized according to the relevant literature [10,[16][17][18][19]. The spectral data were in agreement with the values obtained in previous research, and the structures were identified from the results of the X-ray crystal structure analysis [20].…”
Section: Experimental 21 Synthesismentioning
confidence: 54%
“…T, T2F, and DCM-T were synthesized according to the relevant literature [10,[16][17][18][19]. The spectral data were in agreement with the values obtained in previous research, and the structures were identified from the results of the X-ray crystal structure analysis [20].…”
Section: Experimental 21 Synthesismentioning
confidence: 54%
“…Indoloquinazolinone has a tetracyclic alkaloid skeleton consisting of a quinazolinone fused to an indole unit and is found in several natural products including tryptanthrin,1a,b phaitanthrins1c and ophiuroidine1d (Figure 1). These alkaloids show various biological activities, including antibiotic,2 antiparasitic,3 anticancer,1c,4 and antitubercular5 activities.…”
Section: Methodsmentioning
confidence: 99%
“…To date, several synthetic methods have been developed to further the biological studies on these natural products and their congeners 1b. Indoloquinazolinones are generally prepared by the coupling of isatin and isatoic anhydride, under basic conditions, although the scope of this method is limited 6.…”
Section: Methodsmentioning
confidence: 99%
“…A triptantrina tem sido isolada de diversas fontes naturais, incluindo plantas, fungos, bactérias e, curiosamente, também em mamíferos (nomeadamente da urina do elefante asiático, Elephas maximus, e do líquido do saco da asa do morcego Saccopteryx bilineata) [4]. De entre as plantas tradicionalmente usadas para produzir corantes, destacam-se as espécies Isatis tinctoria, Polygonum tinctorium, Strobilanthes cusia (índigo Assam), Strobilanthes formosanus (índigo naturalis) e Wrightia tinctoria [4][5][6][7]. Considerando estas fontes naturais, torna-se evidente a existência de uma relação entre a triptantrina e o índigo, um corante icónico usado desde tempos ancestrais até aos nossos dias, por exemplo no processo de tingimento da ganga [8,9].…”
Section: Estrutura E Fontes Naturais Da Triptantrinaunclassified